Promoting Science, Technology, and Engineering Self-Efficacy and Knowledge for All With an Autism Inclusion Maker Program - Martin, Wendy B.; Yu, Jennifer; Wei, Xin; Vidiksis, Regan; Patten, Kristie K.; Riccio, Ariana (Frontiers in Education, 2020)
This paper describes the collaborative development of an inclusive maker program called Inventing, Designing, and Engineering for All Students (IDEAS) and the results of a study on the impact of that program on autistic students and their neurotypical peers. The IDEAS project brought together experts in maker education, autism inclusion, engineering, co-design, and research. Over two years, this group adapted and pilot tested a museum-based maker program so that it could be run as an informal club in autism-inclusion middle schools (students ages 10–14) in a large city in the United States. In the third year, teachers in each school implemented the redesigned program on their own. Researchers conducted a mixed-methods study of the impact of the program on participants. The study used observations and interviews; social interaction analysis, a pre/post survey of science, technology, and engineering self-efficacy and career interest; and a pre/post assessment of understanding of the engineering design process (EDP). Autistic and neurotypical students were in either the treatment condition (if they joined the maker program) or a business-as-usual comparison condition (if they did not join the club). Our analyses of the survey and EDP assessment compared the maker group with the comparison group and showed that participating in the maker program led to improved outcomes in the following constructs: technology and engineering self-efficacy (effect size = .80), technology and engineering interest (effect size = 1.73), vicarious experience (effect size = .57), science appreciation (effect size = 0.21), and understanding of the engineering design process (effect size = 0.44). The maker program benefited neurotypical students more than autistic students on technology and engineering interest and science appreciation, possibly because autistic students started with a high level of STEM interest. Qualitative analysis demonstrated that all students engaged in the EDP and pursued a wide range of interests, that autistic students who struggled in normal school settings were successful in creating their projects and communicating with peers about those projects, and that teachers reported being better able to see what their autistic students were capable of accomplishing when they were freed from the constraints of typical classroom instruction.